Central neuropeptide-S administration alleviates stress-induced impairment of gastric motor functions through orexin-A - Mehmet Bülbül; Osman Sinen; Onur Bayramoğlu (Turkish Journal of Gastroenterology, 2020)
Background/Aims: The novel brain peptide neuropeptide-S (NPS) is produced exclusively by a small group of cells adjacent to the noradrenergic locus coeruleus. The NPSR mRNA has been detected in several brain areas involved in stress response and autonomic outflow, such as amygdala and hypothalamus, suggesting that central NPS may play a regulatory role in stress-induced changes in gastrointestinal (GI) motor functions. In rodents, exogenous central NPS was shown to inhibit stress-stimulated fecal output. Moreover, exogenous NPS was demonstrated to activate hypothalamic neurons that produce orexin-A (OXA), which has been shown to stimulate postprandial gastric motor functions via central vagal pathways. Therefore, we tested whether OXA mediates the NPS-induced alterations in gastric motor functions under stressed conditions.Materials and Methods: We investigated the effect of central exogenous NPS on solid gastric emptying (GE) and gastric postprandial motility in acute restraint stress (ARS)-loaded conscious rats. The OXA receptor antagonist SB-334867 was administered centrally prior to the central NPS injection. The expression of NPSR in the hypothalamus and dorsal vagal complex was analyzed by immunofluorescence.Results: Central administration of NPS restored the ARS-induced delayed GE and uncoordinated postprandial antro-pyloric contractions. The alleviative effect of NPS on GE was abolished by pretreatment of the OX1R antagonist SB-334867. In addition to hypothalamus, NPSR was detected in the dorsal motor nucleus of vagus, which suggest a direct stimulatory action of exogenous NPS on gastric motility.Conclusion: NPS may be a novel candidate for the treatment of stress-related gastric disorders.Cite this article as: Bülbül M, Sinen O, Abueid L, Bayramoğlu O. Central neuropeptide-s administration alleviates stress-induced impairment of gastric motor functions through orexin-A. Turk J Gastroenterol 2020; 31(1): 65-72.